A Bibliometric Study of Research Trends in Arabic Language Bilingualism (1986-2024) - Kosim, Nanang; Fauzia, Eva Lathifah; Safrudin, Ramadhan; Fu'adah, Shofwatul; Siregar, Sri Dewi Priwarti (Institut Agama Islam Negeri Curup, 2025)
This study aims to map the research landscape of Arabic language bilingualism through a comprehensive bibliometric analysis covering the period from 1986 to 2024. The increasing global prevalence of bilingualism, particularly among Arabic speakers in countries where Arabic is not the primary language, underscores the need for a systematic understanding of how research in this field has evolved. This study collected data from the Scopus database and applied bibliometric methods, including citation analysis, co-authorship network mapping, and journal quartile evaluation, using Microsoft Excel, Publish or Perish (PoP), and VOSviewer. The analysis revealed that the United States was the most influential contributor to research on Arabic bilingualism. The year 2018 recorded the highest number of publications, with a total of 16, while 2017 had the highest number of citations, reaching 348, indicating strong research impact. Current research themes emphasize the cognitive benefits of bilingualism, such as improved working memory and problem-solving abilities, and explore their implications in educational and social settings. These findings highlight the ongoing importance of fostering collaborative and interdisciplinary research and suggest that educational policies should incorporate insights from bilingualism studies to enhance language acquisition and development.